Thermal damage of high-temperature sandstone subjected to cooling shock and its effect on capturing acoustic emission signals during fracture. (March 2023) - Ge, Shaokun; Wu, Chunlei; He, Changlin; Wang, Yuheng; Chen, Deliang; Shi, Bobo
Highlights: The study aims at effect of cracks in cooling shock sandstone on AE signal in coal-fire control. The AE attenuation coefficient α related to elastic modulus and crack change rate is derived. The amplified and unamplified AE parameters of cooling shock sandstone are analyzed. Abstract: Most surface collapses in coal fire control project are caused by the weakening of high temperature rocks with the water cooling shock. Using acoustic emission to capture disaster signals timely and effectively is critical to ensure the engineering safety. This study aimed to investigating the thermal damage of high-temperature sandstone subjected to cooling shock and its effect on capturing acoustic emission (AE) signals during fracture. The X-ray diffraction test, scanning electron microscope test and uniaxial compression experiment with AE monitoring were carried out for the raw sandstone and 800 ℃ high-temperature sandstone cooled using water (cooling shock sandstone), respectively, The results showed that the crack density and volume of cooling shock sandstone increased by 8.79% and 2.69%, respectively, and p-wave velocity decreased by 51.83%, compared with those of the raw sandstone. The mechanical strength of cooling shock sandstone decreased, including a 50.68% reduction in elastic modulus. The AE attenuation coefficient α related to the elastic modulus and the crack change rate was derived, providing an approach to count the attenuation of AE signal caused by thermal damage for cooling shock sandstone. Increasing the preamplifier amplification factor is feasible to improve the accuracy for monitoring the fracture of cooling shock sandstone in coal-fire control project.